Employer Discrimination: Evidence From Self-Employed Workers - Moore, Robert L. (The Review of Economics and Statistics, 1983)
During the last two decades the issue of equality according to sex and race has become one of increasing importance to economists. An extant literature on the economics of discrimination began with the pioneering work of Becker (1957). This paper is an attempt to shed further light on the extent of employer discrimination by sex and race by comparing the earnings of self-employed workers to their wage and salary counterparts. In short, if employer discrimination is a principal source of discrimination against blacks and women, then we would expect the black/white and female/male earnings ratios to be higher for the self-employed compared to their wage and salary counterparts. No discrimination of this type is applicable to self-employed workers. In addition, blacks and women should be relatively overrepresented among the self-employed compared to wage and salary workers in the economy. Section II of this paper further elaborates on this indirect method to estimate the extent of employer discrimination in the labor market for blacks and women. In section III, the results of this method are presented using the 1978 Current Population Survey as the data source. Results indicate the black/white and female/ male earnings ratios are no larger for the self-employed compared to their wage and salary counterparts, even after making various attempts to adjust for differences in other variables that affect earnings, and to limit the influence of consumer discrimination on the results.